PERAN WORLD TRADE ORGANIZATION (WTO) DALAM MENYELESAIKAN SENGKETA PERDAGANGAN INTERNASIONAL - Rubiyanto Rubiyanto (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
International trade disputes that occur require an international institution to supervise and become the party that has the role to solve the problem. WTO as a world trade organization has an important role in efforts to resolve international trade disputes. Based on the discussion it can be concluded that the WTO as a world trade organization has an important role in resolving international trade disputes. Procedure for resolving international trade disputes. Procedures for resolving international trade disputes within the WTO framework can be carried out through the consultation stage Panels Formation, Panel procedures, Adoption of panels report, Appellate review, and Implementation.